2022
DOI: 10.1016/j.jaci.2021.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance development in cow’s milk–allergic infants receiving amino acid–based formula: A randomized controlled trial

Abstract: Regeneron; serves the American College of Allergy, Asthma, and Immunology as deputy editor of the Annals of Allergy, Asthma, and Immunology and is a member of the American Board of Allergy and Immunology outside the submitted work; and is on the medical advisory board (unpaid) of the International FPIES Association. L. Lange Background: Tolerance development is an important clinical outcome for infants with cow's milk allergy. Objective: This multicenter, prospective, randomized, doubleblind, controlled clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 40 publications
4
49
1
Order By: Relevance
“…Although some preclinical studies in murine asthma models did investigate the effect of certain fibers on microbiome composition in association with asthma prevention, most studies did not investigate this. However, the prebiotic fibers that were used have already been shown clinically to modify the microbiome and to promote the growth and activity of lactobacilli and bifidobacteria [150,[152][153][154][155][156]. Furthermore, concentrations of SCFAs in the faeces/cecum were not investigated in most studies, and only one study reported modulation of SCFA levels in the lung following fiber treatment [112].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some preclinical studies in murine asthma models did investigate the effect of certain fibers on microbiome composition in association with asthma prevention, most studies did not investigate this. However, the prebiotic fibers that were used have already been shown clinically to modify the microbiome and to promote the growth and activity of lactobacilli and bifidobacteria [150,[152][153][154][155][156]. Furthermore, concentrations of SCFAs in the faeces/cecum were not investigated in most studies, and only one study reported modulation of SCFA levels in the lung following fiber treatment [112].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared to the placebo control, the synbiotic supplementation significantly modulated the intestinal microbiota by increasing the percentages of beneficial Bifidobacterium spp., while reducing unfavorable Clostridium liuseburense/Clostridium histolyticum and Eubacterium rectale/Clostridium coccoides [152,153]. Several trials in infants with suspected non-IgE mediated cow's milk allergy [154] or with a confirmed IgE-mediated cow's milk allergy [155] have been initiated. Here, a synbiotic blend combining scFOS/lcFOS and B. breve M-16V was added to infant formula which resulted in an increase in faecal Bifidobacterium spp.…”
Section: Clinical Evidence Early Lifementioning
confidence: 99%
See 1 more Smart Citation
“…This multicenter study was designed and conducted in accordance World Medical Association (WMA) Declaration of Helsinki and the International Conference on Harmonization guidelines for Good Clinical Practice 18 . The following national ethics committees, institutional review boards and regulatory authorities approved the study protocol and amendments: Written informed consent for the collection and analysis of the data was obtained from the parents of all infants included in this study 18…”
Section: Ethics Approvalmentioning
confidence: 99%
“…Several studies have shown fewer respiratory tract infections and otitis media (ear infections) (measured as adverse event outcomes) in infants with CMA receiving a hypoallergenic formula with HiMOs (2 FL and LNnT) [49], as well as with the specific synbiotic mixture scFOS/lcFOS and B. breve M-16V [47]. Synbiotic usage was also associated with reduced overall medication use, including antibacterials and anti-infectives [47,48,50].…”
Section: The Effect Of Prebiotics and Synbiotics On Infection Outcomes In Infants With Cmamentioning
confidence: 99%